Application of solid lubricant for enhanced frictional efficiency of deep drawing process. (January 2022) - Jivan, RB; Eskandarzade, M; Bewsher, SR; Leighton, M; Mohammadpour, M; Saremi-Yarahmadi, S
Manufacturing processes are usually energy intensive, contributing to the global carbon dioxide emissions. Deep Drawing is one of the most common types of sheet metal forming processes with great potential for energy efficiency improvement. In this paper, the optimised combination of molybdenum disulphide (MoS2 ) and graphite is proposed as a solid lubricant to reduce the punching force and energy consumption of deep drawing process. Different mixtures of MoS2 and graphite are prepared and their tribological performance are measured using experimental tests on tribometer. In order to investigate the friction reduction rate in deep drawing process, finite element simulation of the drawing process is performed. Results show that friction reduction using proposed combination of lubricants has significant effect on punching force and would provide greater process efficiency.